Needs Analysis of the Development Cooperative Project-Based Learning Models in the Digital Age: Analisis Kebutuhan Pengembangan Model Cooperative Project Based Learning di Era Digital - febriyanno Suryana; Abna Hidayati (Journal of Vocational Education and Information Technology (JVEIT), 2020)
This study aims to Analyze the learning process in programming language courses to get information about the needs of lecturers and students as well as expectations in pedagogical learning. Analyze the need to develop project-based learning models and cooperative-based learning. The research method used was a survey method. Data were collected using questionnaires, interviews and observations. The research sample is S1 Information Systems Study Program students and Lecturers at the Computer Science Faculty of Putra Indonesia University ‘YPTK" Padang. The results of this study obtained the level of mastery of students' pedagogical competencies at this time and the types of learning styles of each student that describe the characteristics of their learning styles. Then, the model used in the development of learning planning is a learning model that can learn students according to student learning styles so as to create student activity in learning, critical thinking, creative, communicative and collaborative in accordance with the demands of 21st century learning. learning that is equipped with quality model books and lecturer manuals that are expected to be able to improve student competency in accordance with the learning outcomes to be achieved.